L’accompagnement professionnel pour développer des dispositifs didactiques innovants en syntaxe et en ponctuation : regards de conseillères pédagogiques - Marie-Hélène Giguère; Marie Nadeau; Carole Fisher; Rosianne Arseneau; Claude Quevillon Lacasse (Recherches en didactique des langues et des cultures)
The study reported in this article was carried out in two phases: the first year followed an exploratory approach for the creation of teaching devices, and the second year tested these devices through a quasi-experimental protocol. The research team, interested with developing and experimenting with teaching devices to improve syntax and punctuation in writing for students aged 10 to 14, was composed of university researchers, doctoral and postdoctoral students, teacher consultants, as well as elementary and secondary teachers in Quebec. All of these members played different roles throughout the study. This article presents the results of a survey questionnaire submitted to the teacher consultants in which the means to support teacher professional development (TPD) were discussed. The stances from teacher consultants show that this collaborative research made it possible to document the effectiveness of a triple TPD support (monthly group meetings, classroom observations with personal feedback, and provided material), while allowing for a shift of traditionally compartmentalized roles in research.